UJI EFEKTIVITAS BAKTERI PELARUT FOSFAT PENGHASIL ASAM SIANIDA ASAL TANAH GAMBUT RIAU DALAM MENGENDALIKAN GULMA DOMINAN PADA TANAMAN KELAPA SAWIT - Tri Septiani; Delita Zul; Mayta Novaliza Isda (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This research aimed to analyze the effectiveness of phosphate solubilizing bacteria (PSB) which are able to produce cyanide acid (HCN) in controlling of predominant weed in the palm oil plantation. This research was conducted from February to July 2014 in the Laboratory of Microbiology, Faculty of Mathematics and Natural Science, University of Riau. The effectiveness of PSB in controlling the growth of Mikania micrantha was performed by inoculating 26 selected PSB isolates into pre-germinated weed based on the Kremer and Souissi method modification. The parameters observed were root length and shoot length of seedling weed. The results showed that PSB isolates tested, in general, were effective to inhibit the growth of root and shoot length of the weed. BB_K9 isolate was the most effective in controlling the weed as it had a strong level of HCN production.